KAJIAN ADSORPSI Cr(VI) OLEH ABU LAYANG AMPAS TEBU TERAKTIVASI H2O2 - , INDAYATMI, S.Pd; , Prof. Dr. Sri Juari Santosa, M.Eng, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Study on the adsorption of Cr(VI) on H2O2 activated bagasse fly ash has been conducted. The study was directed to reveal the effect of activation on the enhancement of pore size and surface area as well as the effect of pH, initial weight of bagasse fly ash and initial concentration of Cr(VI). The study was initiated by washing bagasse fly ash with aquadest and then followed by activation using H2O2 at various concentrations. Characterization was performed using spectroscopy infrared to elucidate the existence of functional groups, and by using surface area analysis to quantifity surface area and pore radius. The concentration of Cr(VI) in solution was analyzed by using spectroscopy UV-Vis at Î»max 540 nm after complexation of Cr(VI) with diphenilcarbazide. Result showed that the activation of bagasse fly ash with H2O2 2 M was able to enhance the surface area from 44,39 m2/g to 46,60 m2/g, volume of total pore from 0,046 mL/g to 0,054 mL/g, and average pore radius from 19,60 Ã to 24,36 Ã. Adsorption of Cr(VI) on bagasse fly ash was optimum at pH 1,5 with adsorption capacity 0,991 mol/g which was slightly higher than that of adsorption capacity of unactivated bagasse fly ash, i.e. 0,989 mol/g.